DEVELOPMENT AND EVALUATION OF TITANIUM DIOXIDE-FREE FILM-COATED TABLETS CONTAINING DROTAVERINE HYDROCHLORIDE - STROZIK, MIROSLAW; STRZEBONSKA, MAGDALENA; GRYCHOWSKA, KATARZYNA; SKIBA, KATARZYNA; ZAJDEL, PAWEL; TATARA, WIKTOR (International Journal of Applied Pharmaceutics, 2026)
Objective: Drotaverine is a spasmolytic drug commonly used for the symptomatic relief of smooth muscle contractions associated with gastrointestinal disorders, biliary dyskinesia and renal colic. In light of the anticipated prohibition of titanium dioxide (TiO2) in pharmaceutical coatings within the European Union, this study aimed to develop 80 mg drotaverine hydrochloride tablets employing an alternative titanium-free coating and to establish a validated analytical method for the determination and characterization of impurities in accordance with regulatory guidelines. Methods: Two tablet prototypes containing drotaverine hydrochloride were manufactured in laboratory scale. A new high-performance liquid chromatography (HPLC) method for impurity determination in titanium-free coated drotaverine hydrochloride tablets was developed and validated according to ICH Q2(R2) guidelines. Stability studies were conducted, and emerging unknown impurity was analyzed using ultra-performance liquid chromatography coupled with mass spectrometry (UPLC–MS) and nuclear magnetic resonance (¹H and ¹³C NMR). Results: During stability testing, an impurity with a relative retention time (RRT) of 2.05 was detected, exceeding the 0.2% threshold set by ICH Q3B(R2) for unidentified impurities. This impurity was identified as 6,7-diethoxy-1-(3,4-diethoxybenzoyl)isoquinoline (perparaldine). Based on its structural characterization, the reporting and qualification threshold for this impurity was proposed to be extended to 0.5%, ensuring acceptable product quality over at least two years of storage. Conclusion: This work demonstrates an innovative approach by combining titanium-free formulation development with advanced analytical elucidation of novel impurities. Moreover, the validated HPLC method ensures regulatory compliance, reliable routine analysis, and robust quality control and stability assessment of this novel dosage form.